Perlakuan Akuntansi Aset Biologis di Perumda Perkebunan Kahyangan Jember - Puspitasari, Leny; Miqdad, Muhammad; Ika Wahyuni, Nining (Jurnal Manajemen dan Organisasi, 2023)
This study aims to analyze the accounting treatment of biological assets and their compliance with the Financial Accounting Standards (PSAK 69) at Perumda Perkebunan Kahyangan Jember and complience accounting standards (PSAK) 69. The goal is to provide further evidence on the challenges of implementing PSAK 69 regarding biological assets, particularly plant-based biological assets. This research is qualitative in nature, characterized as a case study, utilizing data collection methods involving interviews, FGDs (Focus Group Discussions), and literature review. As a result of this research, the accounting treatment of biological assets at Perumda Perkebunan Kahyangan Jember aligns with PSAK 69 concerning recognition and disclosure in financial statements. However, concerning measurement, the biological assets are valued using historical costs as their acquisition price. The primary challenges faced by Perumda Perkebunan Kahyangan in measuring its biological assets stem from the absence of fair value standards and the high cost involved in valuing these assets.